The effect of negative user-generated content on consumer-based brand equity : comparing brand loyal versus non-loyal customers in the luxury wine market - Wouters, Claire (School of Management Studies, 2016)
With the rise of user-generated content (UGC), negative UGC could have disastrous consequences for brands: One single post could easily spread like a virus, might even go viral and brand managers have no power in limiting the damage. Negative UGC contributes towards an overall negative brand perception, which harms the process of building long-term consumer-based brand equity (CBBE). CBBE is especially relevant for luxury brands, where decisions are heavily reliant on brand perceptions, and perceptions contrary to or different from exclusivity could be established. Luxury wines, in particular, are complex products in the mind of the consumer: wine customers are overwhelmed by too many choices in wine brands with very few objectives decision cues. While CBBE is critical in an extremely competitive wine market, little research has been done on CBBE of luxury wines. This study therefore questions whether CBBE is affected through negative UGC, and if that effect is different for brand loyal versus non-loyal customers. The "love becomes hate" argument proposes that loyal consumers are more impacted by extreme negative UGC, because betrayal in brand trust leads to strong CBBE damage. The "love is blind" argument, on the other hand, proposes that loyal customers are more forgiving towards negative UGC because of their relationship with the brand. Moreover, non-loyal consumers are more influenced by negative UGC, since they exclude brands more easily in a decision-making process after consuming negative UGC. Previous researches regarding CBBE have not found evidence yet of how negative UGC impacts the perception of brand loyal and non-loyal wine consumers. This study therefore attempted to better understand this phenomenon in the luxury wine context. In order to truly understand the impact of negative UGC on CBBE, use is made of Aaker's four-asset CBBE model. This model proposes that CBBE consists of brand awareness, brand associations, perceived quality and brand loyalty. This study used an experimental research design and 154 respondents participated in a quasi-experimental design that tested the effect of fictitious negative UGC, that appeared on Facebook, on CBBE. This study found that negative UGC reduces CBBE and customers' perception of the luxury brand is damaged after exposure to negative UGC. Brand loyal customers' CBBE had the greatest decrease, which supports the 'love becomes hate' argument. Marketing managers therefore need to understand the risks of UGC on CBBE and set up an online brand strategy in order to know how to act and react on negative UGC to prevent CBBE from being damaged. They also need to pay particular care in managing loyal customers' exposure to negative UGC.